DNA barcoding to resolve phylogenetic relationship in Myristica spp. - Swetha, V P; Sheeja, T E; Sasikumar, B (Journal of Spices and Aromatic Crops, 2020)
Myristica is the largest and primitive genus of the taxonomically complex family Myristicaceae. DNA barcoding was used to study the evolutionary relationship between Myristica spp. and other genera of Myristicaceae. The barcoding loci namely, rbcL, matK, psbA-trnH, ITS and multilocus combinations were tested to assess their phylogenetic relationship. psbA-trnH locus revealed information regarding the relationship of species in Myristica genus. M. fragrans was found to be closely related to M. beddomei, M. amygdalina, M. andamanica1, whereas M. Fatua was found to be distinct from M. malabarica. Gymnocranthera and Knema species were found to share sister relation with other Myristica spp.